THE EFFECT OF FIRM AGE, INSTITUTIONAL OWNERSHIP, LEVERAGE, PROFITABILITY, FIRM SIZE, AND PROPER ON CARBON EMISSION DISCLOSURE - Erni Erdawati; Monica Rahardian Ary Helmina; Ade Adriani (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
Climate change has become one of the most critical environmental issues, closely linked to the contribution of carbon emissions generated by companies. This study aims to provide empirical evidence regarding the factors influencing carbon emission disclosure. The population of this study consisted of energy sector companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period. The sampling technique employed was purposive sampling, resulting in a total of 87 research observations. This study utilized secondary data obtained through documentation techniques. Data analysis was conducted using multiple linear regression with the assistance of SPSS version 26 software. The results indicate that firm age and firm size have a positive effect on carbon emission disclosure. Meanwhile, other factors, namely institutional ownership, leverage, profitability, and PROPER, do not have a significant effect on carbon emission disclosure. These findings imply that companies need to enhance compliance with environmental regulations related to greenhouse gas (GHG) emissions and climate change to avoid sanctions, fines, or legal consequences resulting from non-compliance. In addition, transparency in carbon emission disclosure can increase stakeholder trust. Furthermore, such disclosure can encourage companies to develop cleaner and more efficient technologies, as well as adopt more environmentally friendly practices to reduce their carbon emissions.